Nilai-Nilai Islam Inklusif Dan Pendekatan Pembelajaran Pendidikan Agama Islam (PAI) Dalam Membentuk Peserta Didik Sebagai Insan Harmoni Dalam Beragama - Toto Warsito (Al-Mau'izhoh, 2023)
Religious education is aimed at forming Indonesian people who believe in and fear God Almighty and have noble character and are able to maintain peace and harmony in inter- and inter-religious relations and develop the ability of students to understand, live and practice religious values that harmonize their mastery in science, technology and art. Even though Islamic religious education (PAI) subjects have been applied since formal educational institutions existed, the phenomena of radicalism and sectarianism still surface as a concern for pruralist national life. This study with a literature approach tries to find theoretical answers regarding inclusive Islamic values and learning patterns of Islamic Religious Education in madrasas and schools that are aimed at forming individuals. which is expected to be able to create individual students who are faithful and pious and have noble character and are able to maintain peace and harmony in inter- and inter-religious relations. Research result; 1) Inclusive Islamic values in principle are Islamic values in the dimension of tawasuf which reflects Islam as a moderate religion (Islam wasathiyah-Moderation Islam); 2) Islamic Religious Education in terms of inclusive Islamic values must be understood as planting, forming, teaching, nurturing, directing and supervising the internalization and actualization of values in the knowledge, morals and behavior of students in five stages; receiving (listening), responding (responding), valuating (giving value and commitment to values), organization (organizing values within oneself), and characterization (values as behavioral attitudes); 3) The learning method for inclusive Islamic values must be an accumulation of exemplary, stories, visits, discussions, simulations, and cooperative methods.